Mental fatigue mediates the relationship between qi deficiency and academic performance among fifth-grade students aged 10–13 years - Wang, Xinzhu; He, Xinyu; Fu, Kaixian (Frontiers in Psychology, 2024)
Background Health has effects on children’s academic performance. Qi deficiency is generally used to assess an individual’s health in the Chinese traditional medicine theory. This study explores the effects of qi deficiency on children’s academic performance and examines whether mental fatigue mediates these effects. Methods A total of 550 students aged 10–13 in fifth-grade were surveyed in a big primary school in Sichuan Province in November 2023 using paper-pencil-based questionnaires. Qi deficiency and mental fatigue were assessed, and exam scores in Chinese and Mathematics were recorded. Pearson’s correlation and linear regression analyses were used to test the mediation model and hypotheses. Results The fifth-grade students had mild qi deficiency (M = 2.09) and a mild state of mental fatigue (M = 2.38) on a five-point Likert scale. The average exam scores in Mathematics and Chinese were 70.07 and 74.44 points out of 100, respectively. Qi deficiency was associated with Mathematics scores (r = −0.37, p < 0.01) and Chinese scores (r = −0.30, p < 0.01), and mental fatigue (r = 0.47, p < 0.01). Furthermore, mental fatigue was associated with Mathematics scores (r = −0.46, p < 0.01) and Chinese scores (r = −0.34, p < 0.01). Linear regression analyses showed that qi deficiency significantly predicted Mathematics scores (β = −0.26, p < 0.01), Chinese scores (β = −0.19, p < 0.01), and mental fatigue (β = 0.41, p < 0.01). When qi deficiency was controlled for, mental fatigue significantly predicted Mathematics scores (β = −0.28, p < 0.01) and Chinese scores (β = −0.17, p < 0.01). Conclusion The mediation model and hypotheses were well supported, indicating that mental fatigue mediated the influence of qi deficiency on academic performance of fifth-grade students. Furthermore, the mediation effect of mental fatigue on Mathematics scores was a little stronger than that on Chinese scores.